Papsmear Examination for Diagnosing PreCancer Lesion in Invisible SquamoColumnar Junction - Nuranna, Laila; Daud, Sulaeman; Purwoto, Gatot; Winarto, Hariyono; Nuryanto, Kartiwa H (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To know the concealed pre-cancer lesion in women with invisible squamo-columnar junction (SCJ) by Papsmear examination. Method: This study was a descriptive cross-sectional design starting from August 2014 to March 2015 at several Public Health Cares in Jakarta. A total of 1,682 subjects were screened by Acetoacetate Visual Inspection (AVI) examination. After the data was collected, the process was continued by verification, editing, and coding. The descriptive analysis showed the percentage of SCJ in age distribution, the percentage of AVI examination based on SCJ, and the percentage of Papsmear examination in invisible SCJ according to negative AVI result. Result: There were 1,484 (88.2%) women with the visible SCJ and 198 (11.8%) women with invisible SCJ. The percentage of invisible SCJ in the menopausal women group was 122 (61,6%); meanwhile, in the non-menopausal women group, it was 76 (38.4%). Almost half of the percentage from visible SCJ was found in menopausal women group 45.8% (103/225 women). The positive AVI result was 4 (7.1%) in the menopausal women group and 52 (92.9%) in non-menopausal women group. The result of Papsmear examination with invisible SCJ were 197 (100%) normal. Conclusion: Almost half of visible SCJ was found in menopausal women group. Most of positive AVI result was found in the nonmenopausal women group. All women with the invisible SCJ have a normal Papsmear result. Keywords: acetoacetate visual inspection, papsmear, pre-cancer lesion, squamo-columnar junction